Evaluation of Tangibles of Domestic Independent Auditing Firms in Hanoi - Duc Tai Do (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
Evaluation of tangibles of domestic independent auditing firms in Hanoi was conducted based on theoretical background, results of research studies in the world and domestic, and opinions of the experts. Both qualitative and quantitative methodologies were employed. Questionnaires were designed with a 5 - points Likert scale. By using seceral statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, Independent T-test and ANOVA, the study has identified and measured five (5) attributes of tangibles of domestic independent auditing firms in Hanoi, Vietnam that have great effects on employees (or in this case study, auditors). There is not, statistically, significant difference in the level of tangibles of domestic independent auditing firms in Hanoi from these different ages and between the mentioned three groups of work experiences. Based on the findings, some recommendations are given for domestic independent auditing firms to improve tangibles